Unified Formula

Created on March 6, 2013, 5:06 p.m. by Hevok & updated by Hevok on May 2, 2013, 5:31 p.m.

From a given Knowledge Base a Unified Formula can be derived.

Knowledge Base:

(∃X) g(X)
(∀X) g(X) → h(X) v i(X)
(∃X) g(X) ∧ k(X)

Prenex Normal Form:

(∃X)(∀Y)(∃Z) ( g(X) ∧ ( ¬g(Y) v h(Y) v i(Y) ) ∧ ( g(Z) ∧ k(Z)) )

Clausal Form:

The Variable Z has to be replaced by a function depending on the Variable Y: (f(Y))

{{ g(X)}, {¬g(Y), h(Y), i(Y)}, {g(f(Y))}, {k(f(Y))}}

Tags: transformation
Categories: Concept
Parent: Canonical Form

Update entry (Admin) | See changes

Comment on This Data Unit